Rare phytobiota of protected areas of Dergachiv and Zolochiv districts of Kharkiv region - Filatova, O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
The study of the phytobiota of the Dergachiv and Zolochiv districts of the Kharkiv region has proved that there are 15 protected areas and 3 perspective territories for building reserves, which are characterized by significant cenotic and floristic diversity. These are meadow, real and shrub steppes; hollows of oak; real and swampy meadows; coastal water and aquatic vegetation, where 4 rare for Ukrainian vegetative groups (Nymphaeeta albae, Nuphareta luteae, Stipeta capillatae, Stipeta pennatae) and 41 species of plants are protected: 10 species listed in the Red Book of Ukraine (RBU): Adonis vernalis L., Anacamptis palustris (Jacq.) R.M.Bateman, Pridgeon et M.W.Chase, Dactylorhiza incarnata (L.) Soo s.l., D. maculata (L.) Soo s.l., D. majalis (Reichenb.) P.F.Hunt et Summerhayes s.l., Iris furcate M.Bieb., Pulsatilla pratensis (L.) Mill. s.l., Stipa capillata L., S. pennata L., Tulipa quercetorum Klokov et Zoz, and 31 species from the Red List of Kharkiv area (RLK): Actaea spicata L., Aconitum lasiostomum Rchb., Clematis integrifolia L., Gentiana cruciata L., Sanguisorba officinalis L., Thalictrum lucidum L. etc. For each of the surveyed areas lists of rare species and plant groups are given. Phytososological analysis shows the degree of representativeness of the rare phytobiota of the investigated areas and the almost direct correlation between the area of the protected area and the quantitative indices of phytodiversity. The greatest degree of rare phytodiversity has been revealed on the territory of the planned Rogozian landscape reserve of about 2 thousand hectares (4 groups from the Green Book of Ukraine (GBU), 7 species from the RBU, 16 from the RLK); somewhat less in the planned hydrological reserve "Snigivsky" (2 groups from GBU, 1 species from the RBU, 6 from the RLK), in the regional landscape park "Vilkhova balka" (2 species from the RBU, 7 from the RLK), in the “Lychane” botanical reserve (1 group from GBU, 2 species from RBU, 2 from RLK) and in the entomological reserve "Udiansky" (6 species from RLK). In other territories, there are no more than three rare species of plants.